Assessing the Quality of Employee Service from the Competency Sector and Organizational Culture - Giska Putri Helmina; Barkah Rosadi; Bambang Sucipto (Trescode Green Organization, 2024)
This study aims to determine the effect of competence and organizational culture partially and simultaneously on the quality of service at the West Bandung Regency Education Office. This type of research is quantitative research with data collection techniques through library research, field research (observations, interviews, and questionnaires). The population in this study were all consumers (service recipients) at the West Bandung Regency Education Office, totaling 50 people. Determining the number of samples in this study using saturated sampling technique. 50 consumers (service recipients) were sampled as respondents at the West Bandung Regency Education Office. Methods of data analysis using multiple linear regression analysis with t-test and F-test. The results of the study concluded that there is an influence of competence on service quality, there is an influence of organizational culture on service quality and there is an influence of competence and organizational culture together on service quality in the Office West Bandung Regency Education.